אביר טוב או רע? מתודולוגיות בחקר פולמוס ולוחמים בכתבים עבריים מאויירים - אופנברג, שרה (מחשבת ישראל, 2022)
In this essay, I will map a range of different methodological approaches to the study of illuminated manuscripts that contain images of warriors and put them in the context of Jewish-Christian polemics, examining the images and the texts together in conjunction with military history. The importance of this study lies in its holistic reappraisal of the manner in which we think about illustrations in connection with text, the Christian milieu, and the possible meaning that the images had for the patron. Going into great detail regarding the displays of warfare allows us to broaden our understanding of the role these images played in the thought of the Jewish patrons and the reasons why they were included. I will apply the methodology of a close examination of weapons in a Jewish context. After deciphering the iconography, I will turn to the textual context and the meaning it affords the images. This article will focus on examples from four manuscripts, all displaying “bad knights,” that is, warriors and knights who represent persecution and the enemies of the Jews; beginning with a close examination of the text and images of a micrography scene from the book of Jeremiah in an Ashkenazi Bible, continuing with the associative nature of images of warriors in the North French Hebrew Miscellany, and finally ending with examples of the wicked son in two haggadahs.